MS- DOS funciones - Duncan, Ray (s/c: Microsoft Express, 1998)
Los temas principales son: Character, File operations, Record operations, Directory operations, Disk management, Process mangement, Memory management, Time and date, Miscellaneous system functions
Incluye bibliografía
Keywords: DOS - Programas de Sistemas